Modelling of the dependence of travel frequency on the length and duration of a journey. Improvement of city passenger transport systems - Butkevičius, Jonas (Transport, 2002)
The carried out research proved that the distribution of urban travel frequency according to the length and duration of a city journey can best be reflected by the Erlang k-distribution function. This function can be employed to predict time by work travel and the time of journeys during the morning rush-hour. The results of the research done by the author show that over 30% of the residents of Vilnius and Kaunas reach work using public transpm1 means. Their travel usually exceeds the normative length, i.e. over 40 min. The obtained statistical data indicate that the current public transpmt systems in Vilnius and Kaunas are inadequate to meet the residents'needs. Therefore the author has suggested a whole complex of various measures to develop the system of the Lithuanian urban passenger Transport. The main improvement measures have been proposed in accordance with the requirements for the passenger Transport as defined by European Economic Community. The implementation of the proposed measures would allow to restore the prestige of the urban passenger transport and encourage its development under the existing market conditions.First Published Online: 19 Dec 2011